The Development of Two Stay-Two Stray Cooperative Learning Instrument on Respiratory System to Improve Scientific Literacy Skills - Sylvani Kumala Ulinnuha; Muslimin Ibrahim; Utiyah Azizah (IJORER : International Journal of Recent Educational Research, 2021)
Science literacy is an ability to understand, communicate science through oral or written, apply and analyze the current scientific issues in society. This study aims to produce a valid, practical, and effective learning tool, and has been carried out using the 4D (Define, Design, Development, and Disseminate) method; however, the Disseminate one wasn’t carried out. The examination was limited in using one group pretest-post test design. The study was conducted within two meetings with 16 who were doing online learning. The data retrieval used a validated instrument. RPP tools with very decent results, LKPD tools (Student Worksheets) with very decent results, and test kits (Pre-test and post-test) with very decent results. As the result, the learning method shows to be very decent, effective, and practical, while the items of the method used are included in the sensitive category ≥0.30.